Biology and Field Efficacy of Billeae atkinsoni (Diptera : Tachinidae), a Potential Pupal Parasite of Marwar Teak Defoliator in Arid and Semi-Arid Areas - Sharma, Meeta; Ahmed, S. I. (Indian Forester, 2000)
Tecomella undulata (Sm.) Seem, a member of the family Bignoniaceae, is one of the co-dominating tree species in the desert forests of Western Rajasthan and adjoining lands of Haryana and Punjab. It is commonly known as "Rohida" or "Marwar Teak" due to its sparking features of drought tolerant and high quality of timber. Seedlings and young plantations of T. undulata are frequently severely attacked by a serious curculionid pest, Patialus tecomella throughout the tract of its distribution in arid and semi-arid areas. A potential pupal parasite, Billeae atkinsoni has been recorded to keep the pest populations below the level of economic threshold. Biology of Billeae atkinsoni has been carried out in the laboratory under three constant temperatures of 25, 30 and 35°C as well as in the outdoor wire-meshed cages of insectary. Oviposition takes place in the anterior half of the host pupa preferably in the mesoor meta-thorax. The act takes 3.30 ± 0.21 m. The egg is whitish-pale, spindle shaped, measuring about 0.30 ± 0.01 mm in length and 0.65 ± 0.01 mm in breadth at the broadest end. Incubation period vary greatly from 18 to 30 hrs., during July to September in the field conditions whereas in laboratory under different levels of temperature, it ranges from 26.38 ± 2.25 to 41.96 ± 2.34 hrs. Larval stages last in 216.15± 11.56 to 336.46± 36.38 hrs.; pupal stage takes 63.65 ± 2.75 to 86.35 hrs. under three constant temperatures. Adult parasites takes 5.50 ± 0.315 minutes for emergence. Mating process lasts in 35.00 ± 2.53 seconds. Sex ratio in the males and females is recorded as 1:2. The maximum percentage of pupal parasitism was observed during the month of September (54.35% and 50.20% during 1995 and 1996 respectively), while minimum was recorded in the month of January (1.65% and 0.50% in 1995 and 1996 respectively). It is concluded that this parasite will have capability of a promising and potential biological controlling agent of P. tecomella in arid and semi arid areas.